Additive Manufacturing of Polyurethane (PU)/Halloysite Nanotube (HNT) Shape Memory Nanocomposites - Nugroho, Wendy Triadji (Curtin University, 2023)
My project investigated the influence of halloysite nanotubes (HNTs) and processing parameters on dimensional accuracy and surface quality, mechanical properties, thermal properties, chemical properties and shape memory behaviour of 3D printed polyurethane (PU)/HNT nanocomposites and corresponding re-entrant (RE) structures. In relation to this, tensile, hardness, abrasion resistance, compression as well as shape memory tests were performed to reveal 3D printed PU/HNT nanocomposite properties by involving Taguchi method and Pareto ANOVA.